In search of competitive givers. (22nd January 2022) - Fielding, David; Knowles, Stephen; Peeters, Ronald
Abstract: Much of the theoretical and experimental research on charitable giving allows for three main types of donor: pure altruists, impure altruists, and pure warm‐glow givers. For none of these types should donations be increasing in the amount donated by others: there is no room for "competitive giving". We design an experiment in which a participant chooses how much to donate to an individual recipient of charitable funds, conditional on the donation of another participant, and therefore controls the total donation to the recipient. We find evidence for the existence of competitive givers in addition to the other three types, suggesting a great deal of heterogeneity in individual utility functions. However, the frequency of different types depends on whether participants are told about the average donation in a previous experiment. Revealing this information reduces the frequency of competitive givers, suggesting that some competitive giving is motivated by a desire to conform to a social norm inferred from other participants' behavior.